Distinguishing Homogeneity From Vagueness. (8th December 2021) - Feinmann, Diego
Abstract: The question of whether the gappiness associated with vague sentences is of the same kind as the gappiness associated with homogenous sentences has been raised but not settled. In this article, I set out to fill this gap. To begin with, I examine the arguments that have been given for and against assimilating homogeneity to the phenomenon of vagueness (and contend that none of these arguments, neither the positive nor the negative ones, are conclusive). Next, I present three linguistic tests in which homogeneous and vague sentences come apart very clearly, namely, the disagreement test (§ 3.1), the epistemic test (§ 3.2), and the 'I'm not sure' test (§ 3.3). On the basis of these results, I conclude that homogeneity is best understood as a phenomenon of its own and not as a manifestation of vagueness.